Cardamonin inhibits pro-inflammatory cytokine production and suppresses NO pathway in PBMCs from patients with primary Sjögren's syndrome. (4th March 2018) - Benchabane, Sarah; Belguendouz, Houda; Behairi, Nassima; Arroul-Lammali, Amina; Boudjelida, Abdelhalim; Youinou, Pierre; Touil-boukoffa, Chafia
Abstract: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disorder with a complex pathophysiology primarily affecting exocrine glands, leading to compromised secretory function. Recent studies imply that many inflammatory mediators, such as pro-inflammatory cytokines and nitric oxide, are critical in the development and perpetuation of pSS systemic manifestations. In the current study, we aimed to investigate the ex vivo immunomodulatory effect of cardamonin (C16 H14 O4 ), on pro-inflammatory cytokines, TNF-α, IL-6 and inducible nitric oxide synthase (iNOS) expression during pSS. For this purpose, peripheral blood mononuclear cells isolated from pSS patients and healthy controls were cultured with different concentrations of cardamonin. Cytokine levels were measured by ELISA and NO production was assessed using the Griess method. Inducible nitric oxide synthase expression and NF-κB activity were analyzed by immunofluorescence staining. Our results suggest that cardamonin inhibits TNF-α, IL-6 and NO production and downregulates iNOS expression and NF-κB activation. Collectively, our results highlight the ex vivo immunomodulatory effects of cardamonin on pro-inflammatory cytokine production and NO pathway in pSS patients. Therefore, cardamonin is a potential candidate for controlling inflammation during pSS.